A Sociological Reflection on Queen Jelena of Savoy’s Dossier and the Transformation of Historical Interpretation - Šutović, Milojica M. (Collection of Papers of the Faculty of Philosophy in Priština, 2025)
The paper undertakes a sociological reflection on the phenomenon of “secret files,” which, although often compared to metaphors such as Pandora’s box or the reading of a black box, resists reduction to simple analogy. Such figurative associations risk obscuring the dual threads of sociology and history, woven into the same intellectual fabric. Within a milieu dominated by politics, history has traditionally claimed epistemological superiority, relegating sociology to a subordinate role. This hierarchy becomes particularly evident in analyses of the “production” of the past and the “invention of tradition,” manifested through the politicization, revision, or relativization of history. Such processes often neglect the sociological (re)construction and the explanation of causal relationships within historical trajectories, situated in the social milieu of individuals, organizations, events, ideologies, and foreign diplomacy. They also overlook the longue durée of structural forces, conflicts, and international relations, as well as the shifts in historical interpretation that emerge from them. The central questions—how history is produced and who its powerful authors are—point to the cabinets of great powers and the interests of capital. This dynamic is exemplified by the dossier of Jelena of Savoy, Queen of Italy, compiled by Stalin’s secret service, which documents her collaboration with the Tsarist secret service. The publication of Jelena’s dossier opens new possibilities for a more comprehensive interpretation of Russo-Balkan relations.